WHERE IS THE METAPHORICAL STYLE IN THE NOVEL AYAH HEADING?: A COGNITIVE STYLISTICS APPROACH - Ayu Imrotulhasanah; M. Hasbullah Ridwan (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2026)
This study aims to describe the form, conceptual meaning, and stylistic function of metaphors in the novel Ayah, Ini Arahnya ke Mana, Ya? through a cognitive stylistic approach. This study is motivated by the importance of metaphors as conceptual tools that not only function as language sweeteners, but also represent how characters understand life experiences, emotions, social relations, and various psychological dynamics they experience. The method used in this study is a qualitative descriptive method with a cognitive stylistic approach. The research data are in the form of words, phrases, clauses, sentences, and metaphorical expressions found in the novel, while the data source comes from the novel Ayah, Ini Arahnya ke Mana, Ya?. The data collection technique is carried out through the listening method with reading and note taking techniques. Data analysis is carried out through the stages of identification, classification, interpretation, and drawing conclusions based on the conceptual metaphor theory of Lakoff and Johnson. The results of the study show that the metaphors in this novel are dominated by three types of conceptual metaphors, namely ontological metaphors, orientational metaphors, and structural metaphors. Ontological metaphors are used to concretize emotional experiences, inner conflicts, and psychological conditions of characters. Orientational metaphors represent emotional states through spatial orientation, such as up down and near–far. Meanwhile, structural metaphors map life experiences through the concepts of travel, war, and navigation. The research findings indicate that metaphors play a significant role in constructing themes of loss, the search for identity, father–child relationships, and the struggle for the meaning of life. This research's contribution lies in the integration of stylistic and cognitive linguistic studies in the analysis of contemporary Indonesian literature, thus revealing the relationship between language, embodiment, and cognitive processes in the formation of narrative meaning. Keywords: conceptual metaphor, cognitive stylistics, novel.